2004
DOI: 10.1021/jp031167s
|View full text |Cite
|
Sign up to set email alerts
|

Surface Behavior of Alumina-Supported Pt Catalysts Modified with Cerium as Revealed by X-ray Diffraction, X-ray Photoelectron Spectroscopy, and Fourier Transform Infrared Spectroscopy of CO Adsorption

Abstract: The effects of the carrier and pretreatment temperature on the oxidation state of Ce and Pt were evaluated in Pt/Al 2 O 3 , Pt/CeO 2 , and Pt/CeO 2 -Al 2 O 3 catalyst samples with various CeO 2 loadings by applying the following spectroscopic techniques to the samples: X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared (FTIR) spectroscopy of CO adsorption. XRD showed that ceria agglomerates at high CeO 2 loadings (>3 wt %) and at a high temperature of calcination. X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 65 publications
4
67
0
3
Order By: Relevance
“…3B. In the spectra, there are six peaks corresponding to three pairs of spin-orbit doublets similar to spectrum of oxidized CeO 2 as previously described elsewhere [20,21]. The 3d 5/2 features at 881.8, 887.3 and 897.8 eV correspond to v , v II and v III components, respectively.…”
Section: Resultssupporting
confidence: 69%
“…3B. In the spectra, there are six peaks corresponding to three pairs of spin-orbit doublets similar to spectrum of oxidized CeO 2 as previously described elsewhere [20,21]. The 3d 5/2 features at 881.8, 887.3 and 897.8 eV correspond to v , v II and v III components, respectively.…”
Section: Resultssupporting
confidence: 69%
“…The energy regions of Ce 3d, Sn 3d 5/2 and Pt 4d 5/2 core levels in calcined and reduced (at 473 and 773 K) samples were recorded. Although the most intense photoemission lines of platinum were those arising from the Pt 4f levels, this energy region became overshadowed by the presence of a very strong Al 2p peak, and the Pt 4d lines were thus analyzed instead [21,22]. The fresh calcined samples showed an asymmetric broad Pt 4d 5/2 peak ( Figure 1 with the work reported by Navarro et al [22] where a shift to lower binding energies was found in cerium-containing platinum catalysts.…”
Section: X-ray Photoelectronic Spectroscopymentioning
confidence: 54%
“…Figure 14 shows the XPS data of the calcined, reduced, and spent Pt/CoOx/Al2O3. Here, Pt4d rather than Pt4f data were analyzed, due to the strong interference caused by the Al2p peak [15,38]. The raw data were deconvoluted into three peaks assigned to Pt 4+ [39][40][41], Pt 2+ [42], and Pt 0 [40].…”
Section: Xps Characterization Of Pt Speciesmentioning
confidence: 99%